Dynamics of Indian Antagonist Approach towards CPEC and Its Implications for Pakistan - Kamran, Muhammad; Mahsood, Asma Khan (Mediterranean Journal of Social Sciences, 2021)
China Pakistan Economic Corridor (CPEC) is considered as a game-changer for Pakistan and for the whole region. The whole region of Pakistan can take benefits of the projects of CPEC carried out under the umbrella of One Belt One Road initiative. This paper is aimed to explore the regional dynamics of CPEC and Indian antagonistic role towards this project. Pakistan is one of the prime states in China one belt one road initiatives. China is executing a multiyear investment in multibillion dollars program and termed it China Pakistan Economic Corridor. Several projects are included in this plan for instance Industry, communication infrastructure and energy which cost almost USD 46 billion. It is expected that CPEC will contributes remarkably in reducing poverty and socio-economic development of Pakistan. Thus, keeping in view, the benefits of CPEC, most of the analyst claimed it to be the most important mega project in Pakistan. They also claim that it will greatly benefit the people of both countries i.e. Pakistan and China. Received: 28 October 2020 / Accepted: 5 December 2020 / Published: 17 January 2021